Digitally printed strain gauges on 3D metallic objects for pressure sensing - Roudenko, Jewgeni; Häußler, Felix; Franke, Jörg; Reichenberger, Marcus (2023 15th International Congress Mechatronic Integration Discourse (MID), 2023)
In this study digitally printed carbon and silver strain gauges were examined regarding adhesion, topographical properties and their strain sensitivity on aluminum 2D-objects, in the form of tensile test bars and on metallic 3D-objects, in the form of hollow aluminum cylinders. Both sample types were coated with UV-cured dielectric layers via piezo jet printing. All samples showed good adhesion between the dielectric layer and aluminum with removed area values below 1 %. Piezo jet printed carbon sensing grids of 30 μm thickness also showed good adhesion to the dielectric layers after tapetest. Aerosol jet printed silver grids of 2 μm thickness required higher sintering temperatures and two printing passes for good cohesion and adhesion to dielectric layers. The sensitivity of carbon samples was 6.71±0.62 and 8.67±0.79 on 2D-objects and 3D-objects, respectively. Therefore, showing an acceptable correlation with 3D-experiments. The sensitivity of silver samples was 1.91±0.23 and 2.10±0.24 on 2D-objects and 3D-objects, respectively. Therefore, showing a good correlation with 3Dexperiments. Due to a high temperature coefficient of resistance of printed silver (0.276 %/°C), such strain gauges also can be implemented for temperature sensing, because they showed very good response and stability during temperature cycling tests in the range from -40°C to +100°C.
CRIS-Team Scopus Importer:2024-12-16
Keywords: 3D substrate; aerosol jet; carbon paste; dielectric; piezo jet; pressure sens; printed electronics; silver nanoparticle ink; strain gauge